Future Path Presentation to Passengers of an Autonomous Wheelchair Using Vibrotactile Feedback - Yusuke Higashi; Hiroyuki Takai; Tetsushi Ikeda (Sensors)
While autonomous wheelchairs reduce the burden on passengers, automation can make it difficult for them to anticipate the future path of the wheelchair, potentially causing anxiety or discomfort due to unexpected movements. In this study, we define “path” as the geometric trajectory of the wheelchair position, without considering temporal aspects. Providing passengers with information about this future path is crucial, particularly when multiple pedestrians or obstacles are present. Previous studies have primarily focused on presenting only the direction in which the wheelchair turns. In this study, we propose a path presentation method that conveys both the direction and width of turns by varying the duration of haptic apparent motion according to the turning width. The results from the evaluation experiment showed that presenting the future path, including the extent of avoidance maneuvers, improved user understanding and offered a slightly greater sense of security compared to methods that presented only directional information or no feedback at all.